1984
DOI: 10.1128/mcb.4.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of citrate synthase in Saccharomyces cerevisiae may occur at the level of transcription.

Abstract: Pulse-chase labeling in whole cells and cell-free protein synthesis were l,ed to The level of mitochondrial enzymes is finely tuned to the energy demands of the cell. In bakers' yeast (Saccharomyces cerevisiae), the synthesis of respiratory chain components and enzymes of the citric acid cycle is repressed in the absence of oxygen or in the presence of glucose (9,18,24,25). The reverse of this process, the derepression of mitochondrial enzymes, is most easily monitored spectroscopically by the reappearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
(25 reference statements)
3
16
0
Order By: Relevance
“…Specifically, the levels of the enzyme are diminished when cells are grown anaerobically or when fermentable carbon sources are present in the medium (21,23). We have demonstrated that the repression of enzyme synthesis is probably attributable to reduced transcription of the citrate synthase gene (14).…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Specifically, the levels of the enzyme are diminished when cells are grown anaerobically or when fermentable carbon sources are present in the medium (21,23). We have demonstrated that the repression of enzyme synthesis is probably attributable to reduced transcription of the citrate synthase gene (14).…”
mentioning
confidence: 83%
“…1) was identical to that obtained by Suissa et al (25), who isolated the gene on a different basis. These authors determined the nucleotide sequence of the gene and identified a reading frame which was sufficient to encode a protein having a molecular weight of 5.34 x 104, corresponding to the size of the citrate synthase precursor (1,4,14). Since the protein encoded was homologous to porcine citrate synthase and since the presence of the cloned gene on a high-copynumber plasmid increased mitochondrial citrate synthase activity, it is likely that the clone of Suissa et al and our clone encoded mitochondrial citrate synthase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in other eucaryotic cells, in Saccharomyces cerevisiae all the enzymes of the TCA cycle are encoded in the nucleus and are transported into the mitochondrial matrix (34). Like other proteins imported to the mitochondria, citrate synthase is synthesized as a precursor (54 kilodaltons [kDa]) which is cleaved to a mature form (52 kDa) during import (1,3,19). The structure of the mature citrate synthase dimers from pig heart and chicken heart has been determined by X-ray crystallography, and regions of the enzymes involved in substrate binding and catalysis have been identified (7,29).…”
mentioning
confidence: 99%